2016
DOI: 10.1016/j.socscimed.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A chapter a day: Association of book reading with longevity

Abstract: Although books can expose people to new people and places, whether books also have health benefits beyond other types of reading materials is not known. This study examined whether those who read books have a survival advantage over those who do not read books and over those who read other types of materials, and if so, whether cognition mediates this book reading effect. The cohort consisted of 3635 participants in the nationally representative Health and Retirement Study who provided information about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 17 publications
(18 reference statements)
1
58
1
4
Order By: Relevance
“…Of the various modalities of SB, available evidence suggests that in general, self-reported total SB, TV viewing, computer use, and total screen time are negatively associated with physical and psychosocial health indicators in both children and adults [5,12,52]. Although it has been the focus of relatively few studies, the opposite relationship is observed for reading, which is associated with higher levels of academic achievement in children, and increased longevity in adults [5,15]. It is unclear whether these relationships are due to physiological mechanisms, or due to confounding via other variables (e.g., socio-economic status), though at present there is little evidence to suggest that reading per se has a negative impact on health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the various modalities of SB, available evidence suggests that in general, self-reported total SB, TV viewing, computer use, and total screen time are negatively associated with physical and psychosocial health indicators in both children and adults [5,12,52]. Although it has been the focus of relatively few studies, the opposite relationship is observed for reading, which is associated with higher levels of academic achievement in children, and increased longevity in adults [5,15]. It is unclear whether these relationships are due to physiological mechanisms, or due to confounding via other variables (e.g., socio-economic status), though at present there is little evidence to suggest that reading per se has a negative impact on health.…”
Section: Discussionmentioning
confidence: 99%
“…Reading was included given that it is the only form of SB consistently associated with positive health indicators [15]. At present it is unclear whether the health impacts of reading on a screenbased device differ from those of reading a physical book.…”
Section: Suggested Sb Modulementioning
confidence: 99%
See 2 more Smart Citations
“…ACTIVE es el primer estudio randomizado a gran escala que ha demostrado que el entrenamiento cognitivo puede mejorar esta función además de mostrar transferencia a las actividades de la vida diaria (Rebok et al, 2105). Estudios recientes sugieren que leer libros conlleva beneficios cognitivos que, a su vez, influyen sobre la longevidad (Bavishi, Slade & Levy, 2016). La música también se ha considerado como una forma de enriquecimiento ambiental ya que es una experiencia compleja y multisensorial y el entrenamiento musical podría actuar como uno de los principales promotores de la neuroplasticidad a lo largo del ciclo vital (Wan & Schlaug, 2010).…”
Section: Actividades Mentalmente Estimulantes Para Un Cerebro Más Sanounclassified